Acceptance and Commitment Therapy for Health Behavior Change: A Contextually-Driven Approach - Zhang, Chun-Qing; Leeming, Emily; Smith, Patrick; Chung, Pak-Kwong; Hagger, Martin S.; Hayes, Steven C. (Frontiers in Psychology, 2018)
Promoting health behavior change presents an important challenge to theory and research in the field of health psychology. In this paper, we introduce a context-driven approach, the Acceptance and Commitment Therapy (ACT) model which is built on Relational Frame Theory (RFT). The ACT-based intervention aims to promote individuals’ new health behavior patterns through the improvement of the key construct of psychological flexibility, which is defined as the ability to contact the present moment more fully with acceptance and mindfulness as a conscious human being. Building on the psychological flexibility model, implemented through the six core ACT processes, individuals improve maintenance of long term health behavior change through committed acts in service of chosen values while acknowledging and accepting the existence of contrary thoughts, rules, and emotions as part of themselves but not determinant of their behaviors. Taking advantage of this context-driven approach of health behavior change, we recommend researchers and practitioners to design their health behavior change intervention programs based on ACT.